The Relationship between Distress Tolerance, Emotional Labor and Job Satisfaction in Private Hospital Workers - Şerife Güzel; Hilal Akman Dömbekci; Volkan Can Topuz; Müjdat Yeşildal (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
This study aims to examine the state of tolerating the distress of private hospital workers and whether emotional labor is related to job satisfaction. Three scales, namely distress tolerance, emotional labor, and job satisfaction, were used in the study. The research population consists of employees working in a private hospital in Ankara. In this context, the research was carried out with 220 hospital employees. Convenience sampling was used to collect the data. Necessary permissions were obtained for the research. The findings obtained in the study were analyzed through the IBM SPSS Statistics 22 program. T-test and ANOVA test were used because the data took values suitable for normal distribution. While there was no significant difference between tolerating the profession and distress and job satisfaction, a significant difference was obtained with emotional training. As a result, a fragile positive and significant relationship was obtained between distress tolerance and emotional labor. In contrast, a weak positive and significant relationship was found between distress tolerance and job satisfaction and between emotional labor and job satisfaction.